2001
DOI: 10.1055/s-2001-18838
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Principles from Piper fulvescens

Abstract: Activity-guided fractionation of the dichloromethane extract from leaves of Piper fulvescens, using an agar overlay bioautographic method, led to the isolation of three antifungal neolignans identified as conocarpan, eupomatenoid 5 and eupomatenoid 6. The minimal inhibitory concentration of these three neolignans against five fungi strains were determined. Conocarpan showed the widest activity, whereas eupomatenoid 6 was the most active against dermatophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…A presença destas substâncias em espécies da família Piperaceae já havia sido relatada anteriormente (Chauret et. al.,1996Freixa et. al., 2001.…”
Section: Resultsunclassified
“…A presença destas substâncias em espécies da família Piperaceae já havia sido relatada anteriormente (Chauret et. al.,1996Freixa et. al., 2001.…”
Section: Resultsunclassified
“…The compounds (1), 21,29) (2) 7,21,23,29) and (3) 7,21,23,29,36) have been found in other Piper spp. In contrast, the flavonoid (4), was found only in P. solmsianum.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work Freixa and co-workers 23) showed that eupomatenoid-6 and conocarpan exerted considerable activity against some dermatophytes and yeasts. They suggested that the absence of the methoxyl group at position 3 on the phenyl-propenyl-benzofuran structure and the saturation of the carbons 7 and 8 could play important roles in antimicrobial activity.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Conocarpan has been found in other species of Piper [22][23][24][25][26], but the flavonoid orientin is present only in P. solmsianum [14]. For the former compound, antibacterial [14,26], antifungal [13,27] and trypanocidal [28] activities have been described, whereas orientin has exhibited anxiolytic [29], vasorelaxant [30] and antioxidant [31] properties.…”
Section: Discussionmentioning
confidence: 96%